Community Structure of Transplanted Corals by Shelf Method at Bangsring Beach, Banyuwangi - Samuel, Pratama Diffi; Utomo, Anisa Dwi Riskiani; Handziko, Rio Christy; Dewi, Citra Satrya Utama (El-Hayah:Jurnal Biologi, 2025)
Coral reef ecosystems that have been damaged require restoration actions. The study's goal was to identify transplanted coral species on Bangsring Beach, as well as to assess the importance of community structure and community role. Location is determined through selective sampling and direct data capture. Descriptive data analysis, including the diversity index, uniformity, and dominance. The community's part was determined through interviews and questionnaires distributed to the residents of Bangsring. Corals transplanted at Bangsring Banyuwangi Beach include 12 genera and 30 species of coral. The Acropora genus includes Favia, Merulina, Pavona, Pocillopora, Porites, Stylophora, Turbinaria, Nepthea, Tubipora, and Hetroxenia. Block 4 has the greatest diversity index (2.75), followed by blocks 3, 2, 5, and 1. Coral species diversity was relatively high throughout all blocks, with no dominant species. The role of local communities cannot be ruled out in the sustainability of coral reef conservation activities. The community's and managers' active participation in coral transplantation at Bangsring Beach is critical to its success. The transplanted corals at the Bangsring Beach Area are monitored on a regular basis to observe changes in the coral community structure.